A multiple stakeholder-based target-oriented robust optimization approach for post-departure aircraft rerouting problem - Bongo, Miriam F. (Animo Repository, 2021)
Multiple stakeholders involved in the decision-making process have inherent interests that are sought to be maximized along with the collective goals specified by the organization as a whole. Due to the nature of these interests being diverse and often conflicting, an apparent conflict of interests emerges which results to an even greater chaotic situation among stakeholders. One school of thought that investigates such behavior of individuals in an organization - that of stakeholder theory – has explicitly pointed out the need for a scheme to balance the interests of individuals. Despite the introduction of several analytical and optimization tools that aim to put the perspective of stakeholders into balance, there appears to be an inadequacy of frameworks that objectively incorporates the interests of stakeholders into a single metric. Such tools either focus on a single perspective decision process or one without an account for uncertain parameters which also play a crucial role in the decision-making. To advance this significant gap in the literature, this paper proposes a multiple stakeholder-based target-oriented robust optimization (MS-TORO) model which aggregates the interests of stakeholders into a single model with account for uncertainty. The conceptual and mathematical properties of the classical TORO model is used as a part of the MS-TORO framework to generate a satisfying solution with respect to the interests of multiple stakeholders. In order to demonstrate the applicability and validity of the proposed MS-TORO model, a hypothetical case study is performed in the decision process involving post-departure aircraft rerouting problem. The system of the rerouting process involves multiple stakeholders (i.e., airport management, airline industry, and air traffic management) each with inherent interests and an overall goal valued. Furthermore, this system also entails uncertainty in capacity should cases of weather disruptions occur at any point of the en-route phase. Implementing the proposed MS-TORO model provided solutions to the post-departure aircraft rerouting problem which satisfies the interests of multiple stakeholders as represented by the target minimizing the deviation metric from the deterministic optimal solutions of individual stakeholders. The proposed model not only confirmed the preferences of stakeholders in instances when a common route is selected but also showed non-biased solutions, thereby, adequately balancing such diverse and conflicting interests.